KONSEPTUALISASI ASSESSMENT AS LEARNING SEBAGAI INSTRUMEN PENUMBUHAN KARAKTER SISWA - Kistanti; Maratus Shalihah; Kharismatul Khasanah; Nisfu Istiqomah; Afroh Rozana; Ridho Riyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to conceptually examine Assessment as Learning (AaL) as an instrument for fostering student character through a synthesis of various theories and previous research findings. This study focuses on the nature and characteristics of Assessment as Learning, the character values developed through assessment activities, the design of instruments oriented toward character building, as well as the challenges and strategies for its implementation in schools. The study employed a literature review method using a narrative approach. Data were obtained from various scientific articles, books, conference proceedings, and relevant documents, then analyzed using content analysis techniques through a process of information collection, reduction, grouping, interpretation, and synthesis. The results of the study indicate that Assessment as Learning can support the development of students’ character through active engagement in self-assessment, peer assessment, reflection, and the utilization of feedback. This approach contributes to the development of character traits such as academic integrity, responsibility, independence, open-mindedness, social empathy, and self-regulated learning skills. In addition, the implementation of Assessment as Learning requires authentic assessment instruments, transparent evaluation criteria, a culture of continuous reflection, and teachers’ competence in facilitating the assessment process. Thus, Assessment as Learning not only serves as a formative assessment approach but also becomes an effective strategy for integrating the assessment process with the development of students’ character.